1941
DOI: 10.1085/jgp.24.4.447
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Studies on Human Red Blood Cells

Abstract: These experiments were made to obtain more information about the surface of the red blood cell. Since "surface" means different things to different people, we shall define our meaning now. Strictly speaking, the surface studied by electrophoresis is the surface of shear between the cell (moving in the electric field) and the surrounding medium, for it is the potential at this surface which is the electrokinetic potential. But since this potential has its origin in the charged groups possessed by the cell membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

1953
1953
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(24 citation statements)
references
References 5 publications
(4 reference statements)
5
19
0
Order By: Relevance
“…For some time, it has been realized that the net negative charge of the human erythrocyte is due to strongly acidic groups. Furchgott & Ponder (1941) suggested that a phospholipid, possibly cephalin, was responsible for the negative charge. Up to the end of the 1950s many workers agreed in attributing the electrokinetic behaviour of the red blood cell's surface to a membrane component containing ionizable phosphate groups, probably associated with a phospholipid system (Bangham, Pethica & Seaman, 1958; Engstrom & Finean, 1958).…”
Section: (I) Electrophoresis Of Intact Cellsmentioning
confidence: 99%
“…For some time, it has been realized that the net negative charge of the human erythrocyte is due to strongly acidic groups. Furchgott & Ponder (1941) suggested that a phospholipid, possibly cephalin, was responsible for the negative charge. Up to the end of the 1950s many workers agreed in attributing the electrokinetic behaviour of the red blood cell's surface to a membrane component containing ionizable phosphate groups, probably associated with a phospholipid system (Bangham, Pethica & Seaman, 1958; Engstrom & Finean, 1958).…”
Section: (I) Electrophoresis Of Intact Cellsmentioning
confidence: 99%
“…These latter authors confirmed that that the red cell is negative down to pH 3.6 and continuing the curve found that it is isoelectric at pH 1.7. On the same graph Furchgott and Ponder showed that lipid‐extracted stroma protein of red cells is isoelectric at pH 4.7 while a suspension of red cell lipids is isoelectric at pH 2.6. In Fig.…”
Section: Studies With Erythrocytesmentioning
confidence: 89%
“…They also were aware that there is no significant difference in mobility between individuals ‘even in late pregnancy or in a number of cases of primary and secondary anaemias’. In using electrophoretic measurements to deduce the chemical constitution of the cell surface Abramson and colleagues drew attention to the work of Furchgott and Ponder , who extended their work on pH‐mobility curves at constant ionic strength. These latter authors confirmed that that the red cell is negative down to pH 3.6 and continuing the curve found that it is isoelectric at pH 1.7.…”
Section: Studies With Erythrocytesmentioning
confidence: 99%
“…groups imparting a negative charge in eukaryotic cells comprise usually carboxyl, sulfate and phosphate residues [6,[10][11][12][13]. A common component which can be detected by the CIH reaction at low pH (1.8) is sialic acid.…”
Section: ( Canavalia Ensif Ormis)mentioning
confidence: 99%